2021
DOI: 10.3389/fcell.2021.640712
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Gene Expression of Imprinted and X-Linked Genes: A Link to Poor Development of Bovine Haploid Androgenetic Embryos

Abstract: Mammalian uniparental embryos are efficient models for genome imprinting research and allow studies on the contribution of the paternal and maternal genomes to early embryonic development. In this study, we analyzed different methods for production of bovine haploid androgenetic embryos (hAE) to elucidate the causes behind their poor developmental potential. Results indicate that hAE can be efficiently generated by using intracytoplasmic sperm injection and oocyte enucleation at telophase II. Although androgen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 104 publications
5
17
0
Order By: Relevance
“…On the other hand, as previously reported (Aguila et al, 2021;Hu et al, 2015;Latham et al, 1994;Ogawa et al, 2006;Sotomaru et al, 2001), we report perturbed imprinting expression patterns during uniparental development with the overexpression of maternally expressed imprinted genes in parthenotes and overexpression of paternally expressed imprinted genes in androgenotes, consistent with the notion that the absence of the reciprocal parental allele leads to the overexpression of imprinted genes. This differential imprinting expression pattern of haploid embryos determines not only the parental origin of the embryo (Daughtry & Mitalipov, 2014;Sritanaudomchai et al, 2010) but also its association with developmental outcomes (Aguila et al, 2021;Bos-Mikich et al, 2016;Latham et al, 2002). For instance, embryos with only the maternal genome show altered expression patterns of key enzymes required for epigenetic reprogramming (Aguila et al, 2021;Kono, 2006;Peng et al, 2015;Sagi et al, 2019) In a similar fashion, the bioinformatic analysis revealed a differential profile of pluripotency factors, particularly an unbalanced WNT pathway of overrepresented canonical factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, as previously reported (Aguila et al, 2021;Hu et al, 2015;Latham et al, 1994;Ogawa et al, 2006;Sotomaru et al, 2001), we report perturbed imprinting expression patterns during uniparental development with the overexpression of maternally expressed imprinted genes in parthenotes and overexpression of paternally expressed imprinted genes in androgenotes, consistent with the notion that the absence of the reciprocal parental allele leads to the overexpression of imprinted genes. This differential imprinting expression pattern of haploid embryos determines not only the parental origin of the embryo (Daughtry & Mitalipov, 2014;Sritanaudomchai et al, 2010) but also its association with developmental outcomes (Aguila et al, 2021;Bos-Mikich et al, 2016;Latham et al, 2002). For instance, embryos with only the maternal genome show altered expression patterns of key enzymes required for epigenetic reprogramming (Aguila et al, 2021;Kono, 2006;Peng et al, 2015;Sagi et al, 2019) In a similar fashion, the bioinformatic analysis revealed a differential profile of pluripotency factors, particularly an unbalanced WNT pathway of overrepresented canonical factors.…”
Section: Discussionsupporting
confidence: 92%
“…In mice (Ogawa et al, 2006) and humans (Sagi et al, 2019) androgenetic blastocysts have a lower number of cells and are associated with hindered blastulation. Our previous study also reported a poor blastulation rate (26%) for hAE compared to biparental (80%) or hPE (68%) (Aguila et al, 2021). Notably here, GSK3B inhibition enhanced embryonic competence by increasing the "blastulation rate", seen as the proportion of morulas becoming blastocysts.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Cell count in the blastocyst is associated with embryo quality, resistance to cryopreservation, and ultimately with pregnancy and deliveries after transfer [ 14 , 72 , 73 , 74 ]. The evaluation of the total number of cells showed that the embryos generated under defined conditions showed a quality similar to that obtained in the presence of FBS/BSA.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide the first insights into parthenogenetic blastocyst development in cattle using Zn chelation. In this species, assisted oocyte activation has been used to generate haploid and diploid parthenogenetic [ 28 ] and androgenetic embryos [ 29 ]. Moreover, it is an essential step in SCNT and for assisting round spermatid sperm injection.…”
Section: Discussionmentioning
confidence: 99%